Green Banking: A Bibliometric Analysis of Research Trends, Collaboration, and Future Opportunities - Fatih Nurrochman; Muhamad Subhi Apriantoro (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study aims to map the development, trends, and future research directions of Green Banking by analyzing all publications indexed in the Scopus database from 1933 to 2024. Research Methods: A total of 1,252 documents were identified through a Boolean search, and after filtering for English-language journal articles, 698 documents were analyzed. Data were processed using Excel and RStudio, while visualization of keyword co-occurrence and citation networks was conducted using VOSviewer. Results: The findings reveal an annual publication growth rate of 5.2%, with a significant surge in 2022 (101 papers) and 2024 (175 papers). China emerged as the leading contributor with the highest number of publications, while Tsinghua University was the most prolific institution. Zhang B. was identified as the most productive author. Conclusion: This study provides a comprehensive overview of the evolution of Green Banking literature and can serve as a foundational reference for future research in sustainable finance.